Impact of Contrast-Induced Nephropathy on Long-Term Renal Function after Coronary Angiography and Contrast-Enhanced Computed Tomography - Moriya, Hidekazu; Mochida, Yasuhiro; Ishioka, Kunihiro; Oka, Machiko; Maesato, Kyoko; Yamano, Mizuki; Suzuki, Hiroyuki; Ohtake, Takayasu; Hidaka, Sumi; Kobayashi, Shuzo (Cardiology and Cardiovascular Medicine, 2022)
Background: It remains unclear whether contrast-induced nephropathy (CIN) has a prognostic impact on subsequent renal dysfunction and whether deteriorating renal function is a risk factor for CIN. This study aimed to evaluate the occurrence of CIN in patients with pre-existing renal dysfunction and investigate the long-term effects of worsening renal function after coronary angiography or contrast-enhanced computed tomography (CT). The prognostic factors of worsening renal dysfunction were also analyzed. Methods: This was a prospective cohort study of patients at risk for CIN, defined as an estimated glomerular filtration rate (eGFR) <60 mL/ min/1.73 m2 on coronary angiography or eGFR <45 mL/min/1.73 m2 on contrast-enhanced CT. Serum creatinine levels and the 2-year prognosis were evaluated. CIN was defined as an increase in serum creatinine level by more than 0.5 mg/dL or a 25% increase from the previous value within 72 hours after contrast administration. The primary endpoint was the proportion of patients who had serum Cr doubling or induction of dialysis within 2 years according to CIN occurrence. Results: Of the 410 patients, 19 patients developed CIN (8/142 patients on coronary angiography and 11/268 patients on contrast-enhanced CT), and 38 patients had worsened renal function (21/142 patients on coronary angiography and 17/268 patients on contrast-enhanced CT). CIN was not associated with worsening renal function at 2 years. Analysis by renal function at the time of coronary angiography or contrast-enhanced CT (i.e., eGFR ≥30 ml/min/1.73 m2 and eGFR ≤1.73 m2) found no between group difference in the occurrence of CIN. Conclusions: CIN is not a prognostic risk factor for the long-term of chronic kid